EFEKTIVITAS PENDEKATAN KONSTRUKSIVISME TERHADAP PRESTASI BELAJAR EKONOMI PADA MATERI MODEL DIAGRAM INTERAKSI PELAKU EKONOMI SISWA KELAS X SMA NEGERI 1 ULUSUSUA TAHUN PELAJARAN 2023/2024 - Halawa, Elmi (Universitas Nias Raya, 2024)
This research aims to evaluate the learning achievement of tenth-grade students at SMA Negeri 1 Ulususua in economics subject by comparing the use of constructivism approach with PjBL Model learning. The method employed is quantitative research with a pos-test only control design. The research population consists of 27 tenth-grade students, selected randomly using simple random sampling. Data were collected through written tests and documentation. The tenth-grade class is designated as the experimental class. Data analysis is conducted using the t-test statistical analysis. The research findings reveal that the average post-test score of the experimental class is 80.8, while the control class is 67.6. Using a 5% significance level, the t-table value for df = 60 is 2.02 and 5.756. The analysis results indicate that t calculated > t-table, thus rejecting the null hypothesis. Consequently, there is a significant difference between the use of constructivism and non-constructivism approaches towards the learning achievement of economics among tenth-grade students at SMA Negeri 1 Ulususua in the academic year 2023/2024.